Efektivitas Pembelajaran Sejarah Kebudayaan Islam dengan Menggunakan Multimedia Autoplay di Kelas XI Madrasah Aliyah Kota Samarinda - Rumainur, Rumainur; Razak, Abdul (SYAMIL: Journal of Islamic Education, 2020)
The history of Islamic culture is one of the subjects that emphasizes more on historical stories. Multimedia autoplay is one of the media that helps SKI learning more interesting and innovative, not just to present conventional learning. This is in accordance with the development of the industrial revolution era 4.0. The purpose of this research was to determine the effectiveness of learning outcomes of the history of Islamic culture by using multimedia autoplay in class XI Madrasah Aliyah Samarinda City. This type of research used in this research is quasi-experimental design with pretest-posttest control group design. The population in this research were all Madrasah Aliyah, Samarinda City, East Kalimantan Province and the samples used in this research were two classes from three schools namely MAN 2 Samarinda, MA Terpadu Al Uswah, and MA Al Mujahidin with the purposive sampling technique. Data collection techniques used are tests and documentation. The data analysis technique used is the t test with the prerequisites for normality tests using Kolmogorov Smirnov and homogeneity tests using Levene's. Judging from the average learning outcomes, the results of this research are that using Multimedia Autoplay is greater than the conventional method. Thus the used of Multimedia Autoplay is effective against learning outcomes of the history of Islamic culture in Madrasah Aliyah, Samarinda City.